If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -8 = 9x + 8 Reorder the terms: -8 + 8x = 9x + 8 Reorder the terms: -8 + 8x = 8 + 9x Solving -8 + 8x = 8 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -8 + 8x + -9x = 8 + 9x + -9x Combine like terms: 8x + -9x = -1x -8 + -1x = 8 + 9x + -9x Combine like terms: 9x + -9x = 0 -8 + -1x = 8 + 0 -8 + -1x = 8 Add '8' to each side of the equation. -8 + 8 + -1x = 8 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = 8 + 8 -1x = 8 + 8 Combine like terms: 8 + 8 = 16 -1x = 16 Divide each side by '-1'. x = -16 Simplifying x = -16
| -53+2i=-I+73 | | 4m+t= | | 4m+10=2m-6 | | 6-3x=14-7x | | -5(x-3)+2x=6 | | 14(2f)=7(f-2) | | 9y-(11)-(5y)=-25 | | -53-2i=-I+73 | | y/11=17 | | 6x+4=70 | | 2.4(3.1x+4.9)=75.9+0.87 | | m(m-3)=54 | | 5m-7= | | -4-(1-5)-4x-4= | | x/8=-6 | | 7x+17=3x+1 | | x/8=-7 | | 9y-11-5y=-25 | | 10x^2-2x-6=0 | | -6s+-15=15 | | 3=.33-2b | | 3k^2=-12-20k | | 3a-4a=9-4a | | -4-(1-5)=-4x-4 | | 9+9=97+x | | 9(x+1)-3x=2(3x+1)-4 | | 4(s+1)=12(s+3) | | 18-4x=-36 | | 10x+5(x-3)=15 | | 4e^16x=14 | | 6x-12=2x+36 | | -24y-42=18 |